ANALYSIS STUDENTS’ PERCEPTION OF USING MOBILE ASSISTED LAGUAGE LEARNING(MALL) IN READING CLASS - Subur okmaja; Yupika Maryansyah; Ivan Achmad Nurcholis (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aimed to determine students' perceptions of the use of MALL in the reading class on their learning development using mobile phones as a distance learning medium, especially in the 4.0 era and because of the current conditions faced by students such as the advances in technology that must be overcome to maintain the quality of education or education. student. lecturers must take advantage of MALL, this has been aimed at creating an innovative and creative learning environment with an integrated learning system based on faith and piety, as well as science and technology. This study used descriptive qualitative research, because this study was intended to explain and control symptoms, how much influence the use of smart phones or mobile phones has on improving students' academic reading in the reading class, data collection in this study was intended to obtain strong and relevant data, data collection techniques used by researchers was a questionnaire. This research was carried out in the sixth semester students of the English Department at the University of Muhammadiyah Bengkulu. The sample is twenty students Apart from the rapid development of technology, one of the factors supporting the used of MALL in the teaching system in the reading class by lecturers because of the corona virus which requires students to study remotely or study online. The findings of this studied indicate that the use of MALL in the learning process in the reading class is quite helpful for them, this can be seen from the scale obtained by students based on the results of the Guttman scale analysis, the results of 68% according to the interpretation table are in the range of 0.51 – 0.99, so it can be concluded It is said that the perception of students who use MALL in the reading class is good enough. Keywords: Reading Class, MALL, Students’ perception